Investigation of mobility and bioavailability of arsenic in agricultural soil after treatment by various soil amendments using sequential extraction procedure and multivariate analysis - Chatchai Srithongkul (2019)
© 2019 Elsevier B.V. Arsenic (As) partitioning in soil stabilization processes responded differently to various application factors. This research reported on the use of multivariate analysis to assist in the investigation of As partitioning after treatment by various soil amendments. The soil samples were taken from an agricultural area located in a mountainous region of Chiang Mai province in Northern Thailand. The soil amendments were FeSO4, FeCl3, Fe-EDTA and CaCO3 with the application rates of 0 (control), 0.1, 0.5 and 1% w/w. A Sequential Extraction Procedure (SEP), resulting in a total of 8 fractions, was performed on the amended soils to monitor As partitioning. Using the established Partial Least Squares (PLS) model, the distribution pattern of the As partitioning was revealed. It was possible to visualize the stabilization characteristics of the soil amendments. Fe-EDTA had the smallest effect on the soil pH. Notably, CaCO3 possessed the ability to reduce the bioavailability of As; however, it failed to reduce the mobility of the As in the soil. Furthermore, FeSO4 has proven to be the most effective stabilizing agent with regard to the reduction of the bioavailability and mobility of the As in contaminated soil. These findings corresponded to the quantitative results wherein bioavailable As was decreased by up to 60–95% in soil amended with Fe-based amendments, whereas CaCO3 only led to the reduction of 38% when compared with the amount of As in the control soil. In addition, FeSO4 effectively immobilized As with a total increase of 282% for As mobility. However, the degree of As mobility of the soil amended with CaCO3 was not notably different from that of the control soil. The reported procedure is expected to be a new tool for visualizing and predicting the potential effects of the soil amendments in terms of controlling the mobility and bioavailability of As in contaminated agricultural areas.